2004
DOI: 10.1111/j.1365-2257.2004.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for primary splenic low-grade non-Hodgkin's lymphomas

Abstract: The purpose of this comparative study was to evaluate the response of primary splenic low-grade non-Hodgkin's lymphomas (NHL) to chemotherapy, splenectomy, and chemotherapy combined with splenectomy in order to elaborate the optimum treatment modality. A total of 104 patients (age range: 15-82 years) with primary low-grade B-cell NHL of the spleen were comprised by our study. Stage IV disease was determined in 102 (98.1%) cases. Regarding the treatment modality, splenectomy was performed in 14 patients, early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Recent additional modifi cation refers to slight potential involvement of liver and/or bone marrow. Enlarged nodes beyond the splenic hilum indicate advanced disease inconsistent with PSL [10]. Extended range of gross pathological manifestations explains the variety of radiological appearances and relative diffi culty in accurate radiographic diagnostic process identifi ed in our patient.…”
Section: Discussionmentioning
confidence: 85%
“…Recent additional modifi cation refers to slight potential involvement of liver and/or bone marrow. Enlarged nodes beyond the splenic hilum indicate advanced disease inconsistent with PSL [10]. Extended range of gross pathological manifestations explains the variety of radiological appearances and relative diffi culty in accurate radiographic diagnostic process identifi ed in our patient.…”
Section: Discussionmentioning
confidence: 85%
“…However, since the advent of rituximab, some have suggested that splenectomy can be abandoned as first-line treatment for splenic MZL as rituximab alone has 88-100% response rate (23,24). Moreover, Musteata et al suggested that early splenectomy along with combination chemotherapy was the optimal treatment for low-grade PSL, leading to higher response rates, progression-free survival, and OS compared to chemotherapy alone (25). For those unable to undergo splenectomy, local radiotherapy has historically been considered for low-grade PSL (25).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 104 patients with primary low grade non-Hodgkin lymphoma of the spleen concluded that early splenectomy along with the combination of chemotherapy was the optimal treatment due to higher rates of remission, a more prolonged duration of remission and better overall survival rates when compared with splenectomy or splenectomy with a single agent chemotherapy [15] . Most cases of aggressive subtype (DLBC, ALCL) show disease expansion and progression, requiring appropriate chemotherapy.…”
Section: Discussionmentioning
confidence: 99%